Clinical Report: Application of Jiao’s Head Acupuncture in Cervical Spinal Cord Injury Treatment - Cheung, Kwan Yuet; Fang, Dezhang; Chi-Ao Yang, Juno Youn; Tran, Long; Lee, Hansol; Lee, Yeonwoo; Yang, Hye Jin; Dai, Xin; Xu, Bin; Chen, Yemeng (British Journal of Healthcare and Medical Research, 2024)
Objective: This study investigated the efficacy of Jiao’s head acupuncture in the treatment of a 46-year-old male who experienced quadriplegia due to cervical spinal cord injury after a head injury accident. Western medicine predicted that he would be unlikely to walk again, necessitating lifelong reliance on a wheelchair. Following three years of treatment and surgical interventions under conventional Western medical protocols, the patient showed no substantial improvement and continued to require assistance for daily activities. In this case, traditional western approaches did not yield the desired outcomes. Method: The treatment plan mainly used Jiao’s Head Acupuncture for the Motor Zone, Sensory Zone, Foot Motor-Sensory Zone and Balance Zone. It also combined auricular stimulation with traditional acupuncture to target key points. Acupuncture sessions were conducted weekly for one hour. Results: The patient was able to stand up from the wheelchair during 2-3 sessions. The patient used a walker during sessions 7-8 and achieved independent walking under supervision by session 12. Noticeable improvement in muscle tone, range of motion, and mobility were observed within a two-month period. The patient’s muscle strength in the quadriceps and anterior tibia muscles has notably improved from a scale of 1 to 4 out of 5. Discussion: This case study highlighted the efficacy of Jiao’s head acupuncture in restoring motor function in patients with cervical spinal cord injury, helping to repair damaged nerves, especially in cases where western medicine treatment couldn’t see promising positive outcome and is worthy of further research and inclusion in clinical rehabilitation practice.